Answer:
(x+3)²-11=0
Step-by-step explanation:
0=9(x2+6x)-18
0= 9x² +54x-18
0= 9( x²+6x-2) taking 9 common
0= x² +6x-2 (breaking the mid term to find the second element of the square
0 = (x)² +2(x)(3) +(3)² -2 -9 adding and subtracting the second element
0= (x+3)² -11 summing up
Answer:
![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
Step-by-step explanation:
The rate of change is a measure of the slope
Calculate the slope m using the slope formula
m = ![\frac{y_{2}-y_{1} }{x_{2}-x_{1} }](https://tex.z-dn.net/?f=%5Cfrac%7By_%7B2%7D-y_%7B1%7D%20%20%7D%7Bx_%7B2%7D-x_%7B1%7D%20%20%7D)
with (x₁, y₁ ) = (29, 9) and (x₂, y₂ ) = (33, 10)
m =
=
← rate of change
Using the slip and slide method:
2x^2+5x-12
x^2+5x-24
(x+8)(x-3)
(x+8/2)(x-3/2)
(x+4)(2x-3)
Final answer: (2x-3)(x+4)